ヒガシ オングルトウ カキ ニ オケル タイキ カンキョウ トク ニ アリュウサン ガス ノウド オヨビ コウカ バイジン リョウ ニ ツイテ - 遠藤, 陽子; エンドウ, ヨウコ; 唐沢, 栄; カラサワ, サカエ; Endo, Yoko; Karasawa, Sakae (国立極地研究所, 1977)
P(論文) 第15次日本南極地域観測隊の環境科学系観測の一環として,1974年1月12日から2月3日まで,昭和基地周辺の大気環境調査を行った.調査地点は,昭和基地の発電棟を基点として,島内をほぼ扇形状に300mごとに区切り,15地点設置し,調査は亜硫酸ガスを二酸化鉛法で,降下ばいじんをダストジャー法で行った.その結果,亜硫酸ガスは1～30μg/day/100 cm^2 PbO_2であり,地点別の相対的な比較をすると,高い値が得られた地点は,いずれも基地を中心とした300m区域に集中し,基地の風下方向である西南西から南南西方向の区域で高い傾向にあった.降下ばいじん量は,0.2～3.0 g/m^2/monthの範囲で分布していた.降下ばいじん中の鉛,銅,カドミウム,マンガン,ニッケル,鉄およびバナジウムの量はいずれも低濃度であったが,各物質の最高検出値は,ほぼ基地内の地点で認められた. Sulfur dioxide and fall dust in the air were collected from January 12 to February 3, 1974, at Syowa Station. The analysis showed that concentration of sulfur dioxide was from 1 to 30μg/day/100 cm^2 PbO_2. The concentration of sulfur dioxide depended on wind direction and velocity, and high concentration was observed in the area between the station building and 300 m southwest of the station, but other sampling points showed low concentration nearly equal to the background value. The concentration of fall dust was from 0.2 to 3.0 g/m^2/month, but it was independent of wind direction and wind velocity. departmental bulletin paper